Multi-layer Analytical Model and Characteristic Analysis of Axial Flux Permanent-magnet Eddy-current Coupler - Shangguan Xuanfeng; Zhao Zhengwei (Jixie chuandong)
A new analytical framework for the surface-mounted permanent magnet axial flux eddy current coupler is established and the characteristic analysis is carried out. By combining three-dimensional magnetic equivalent circuit approaches,Faraday’s law and Ampere’s law,a electromagnetic analysis model of the axial-flux eddy current coupler is established. In addition to account for the three dimensional parameters,the proposed analytical approach can effectively deal with the complex geometric shape of the model. The discussions of the influence of the material and the thickness of the conductor layer on the applicability of the multi-layer analytical model,the influence of the number of layer are carried out based on the analytical model. The results of three-dimensional finite-element simulation show that the established multi-layer analytical model is precise within a certain range.